1996
DOI: 10.1152/ajpendo.1996.271.1.e96
|View full text |Cite
|
Sign up to set email alerts
|

Perfused skeletal muscle contraction and metabolism improved by angiotensin II-mediated vasoconstriction

Abstract: In the present study, the effects of angiotensin II (ANG II) on tension development and associated metabolism during twitch and tetanic stimulation via the sciatic nerve of the gastrocnemius-plantaris-soleus muscle group of the perfused rat hindlimb were investigated. Rat hindlimbs were perfused at constant flow with an erythrocyte-containing medium equilibrated with 95% air-5% CO2 at 37 degrees C, and determinations of oxygen and glucose uptake, lactate and glycerol release, and 2-deoxy-D-[1-3H]glucose uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
2
21
0
2
Order By: Relevance
“…Inhibition of vasodilatation restricts local blood flow and lipolysis in skeletal muscle tissue (Goossens et al 2004) and glucose oxidation exceeds uptake (Townsend and DiPette, 1993) in those subjects. Elevated plasma and tissue angiotensin II levels in this genotype may facilitate the redirection of blood flow from type I muscle fibres to the type II fibres (Rattigan et al 1996) that are favoured in power performance. Greater plasma and tissue angiotensin II causes a reduction in mitochondrial density (Drexler et al 1992), reduces muscle oxidative capacity (Drexler et al 1992;Mettauer et al 2001) and increases the proportion of fatigue-sensitive fast type II fibres and consequently decreases proportion of slow-twitch, fatigue-resistant type I fibres (De Sousa et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of vasodilatation restricts local blood flow and lipolysis in skeletal muscle tissue (Goossens et al 2004) and glucose oxidation exceeds uptake (Townsend and DiPette, 1993) in those subjects. Elevated plasma and tissue angiotensin II levels in this genotype may facilitate the redirection of blood flow from type I muscle fibres to the type II fibres (Rattigan et al 1996) that are favoured in power performance. Greater plasma and tissue angiotensin II causes a reduction in mitochondrial density (Drexler et al 1992), reduces muscle oxidative capacity (Drexler et al 1992;Mettauer et al 2001) and increases the proportion of fatigue-sensitive fast type II fibres and consequently decreases proportion of slow-twitch, fatigue-resistant type I fibres (De Sousa et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Local AngII is necessary both for angiogenesis [104] and for optimal muscle trophic response to loading [105], and may therefore be necessary for skeletal muscle growth. AngII has been shown to increases muscle strength in rat hindlimb preparations [106]. Our laboratory has shown that, in a cohort of 103 COPD patients, those with the I/I polymorphism of the ACE gene had reduced quadriceps strength compared with those with the D/D polymorphism [107] (Figure 6).…”
Section: Genetic Susceptibilitymentioning
confidence: 94%
“…A kutatók kimutatták, hogy a quadriceps ereje nagyobb mértékben növeke-dett a tréning hátasára a D allélt hordozóknál [17]. Az angiotenzin-II a vér I-es típusú rostok felől a II-es típusú rostok felé történő redisztribúcióját is előidéz-heti [18], amely szintén magyarázatul szolgálhat a D allél és az erőorientált sportágak asszociációjára.…”
Section: Teljesítménnyel öSszefüggő Génváltozatokunclassified